Prevention of VAP: Physiotherapy work with the multidisciplinary team (Research, Society and Development, 2023)
Introduction: Among Healthcare-Associated Infections (HAIs), Pneumonia Associated with Mechanical Ventilation is a serious respiratory infection, which manifests itself 48 hours after the start of Mechanical Ventilation (MV), until its suspension and can cause an increase in hospital expenses and increased length of stay. Objective: to verify the performance of the physiotherapy professional together with the multidisciplinary team with regard to the prevention of Ventilation-Associated Pneumonia (VAP). Methodology: This research is an integrative review of the literature, which was carried out through the use of the descriptors: “Pneumonia Associated with Mechanical Ventilation”, “Hospital Infection”, “Disease Prevention”, “Physiotherapy Specialty”, included articles over the last 10 years, in Portuguese and English. Results: In the databases searched, 364 articles were found, in full text there was a reduction to 314 articles, selected by Portuguese and English and filtered in the last 10 years, 117 articles remained. Of these 117 articles, 7 were chosen, whose themes fit the criteria for the study. Final considerations: In this review, it was possible to identify that physiotherapists are part of the multidisciplinary team and have great importance in preventing VAP. However, the multidisciplinary team needs to work together for the effectiveness of VAP prevention, seeking technical-scientific knowledge and training on the subject and future studies need to research and delve deeper into physiotherapy techniques and their effectiveness in preventing VAP.